The role of ion-neutral collisions in Titan׳s magnetospheric interaction. (April 2015) - Sillanpää, Ilkka; Johnson, Robert E.
Abstract: We have studied the effects of ion-neutral collisions on Titan׳s interaction with the magnetospheric plasma flow and also on the Alfvén wings formed in this super-Alfvénic interaction. We have used the HYB-Titan hybrid simulation model to study the role of charge exchange processes and elastic ion collisions in the interaction region. The simulation runs quantify the ion energy deposited into Titan׳s atmosphere by propagating both the magnetospheric and pickup ions. The results show that the charge exchange reactions between magnetospheric ions and exospheric molecules significantly reduce the energy deposited directly in Titan׳s upper atmosphere by the tracked ions. In addition, the inclusion of the collisional effects between ions and neutral particles causes the nitrogen ion escape from Titan to be reduced by more than a half. Alfvén wings are a major phenomenon in Titan׳s plasma interaction and they are not significantly affected by the ion-neutral reactions. Alfvén wings are shown to create an area of reduced magnetospheric ion density.